PENGARUH PERUBAHAN TATAGUNA LAHAN TERHADAP KARAKTERISTIK HIDROGRAF BANJIR (Studi Kasus DAS Dengkeng dan DAS Jlantah Bagian Hulu Bengawan Solo Kabupaten Sukoharjo, Provinsi Jawa Tengah) - , Yulyana Aurdin ([Yogyakarta] : Universitas Gadjah Mada, 2012)
event The flood on December 26, 2007, in Bengawan Solo, the Province of Jawa Tengah has caused loss and submerged housed of thousands of people. The growing issue in regard to the event indicated that the cause was the changing response of the cathment area to the rain due to the land use changing. The changing of the hydrograph shape and the amount of peak discharge can be interpreted as the form of land use changing consequences. Thus, it is required to have a hydrological analysis to identify the changing of the peak discharge due to land use changing. catchment areas as the critical In this study, hydrological analysis was carried out for Dengkeng and Jlantah catchment areas. The hydrological analysis method used was calculating the measured unit hydrograph (observed) by using the Collins method in the conversion process of rain into flow, calculating the effective rain by using the Soil Conservation Service-Curve Number (SCS-CN) and calculating the planned flood with repetition periods of 2, 5, 10, 25, and 50 years by using the frequency analysis method. The planned flood calculation was carried out for various land use conditions. catchment areas from 2003 to 2009 has not Results of this study showed that the CN value as the determinant variable of the land function in Dengkeng and Jlantah indicated significant improvement changes. Therefore, it is required to rehabilitate forest and critical land as well as to optimally improve the development of the catchment areas in the future by making efforts of land use control. Based on the plans by BPDAS Solo, the results indicated that such rehabilitation influenced the changing of CN value and the losses factor as well as to the effective rain in rain-flow diversity. This was indicated by the declining flood peak discharge in 2025 from 18% to 66%.